2012
DOI: 10.1111/j.1365-2745.2012.01967.x
|View full text |Cite
|
Sign up to set email alerts
|

Artificial selection on flowering time: influence on reproductive phenology across natural light environments

Abstract: Summary1. Flowering time is frequently under selection due to a combination of abiotic, biotic and intrinsic factors. Evolution in response to this selection is likely to have broad effects, altering not only flowering time but reproductive phenology and, potentially, traits throughout the life cycle. We know little about the broader phenotypic changes associated with evolutionary shifts in flowering time, and the extent to which expression of these changes depends on local environmental conditions. 2. After t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 86 publications
1
29
2
2
Order By: Relevance
“…Flowering begins in mid‐summer and fruits ripen and dehisce throughout the fall. Seeds disperse when fruits mature (Galloway & Burgess, 2009) and are nondormant at maturity (Baskin & Baskin, 1984), so the reproductive phenology of maternal plants directly influences offspring germination season (Galloway, 2002; Galloway & Burgess, 2009, 2012). Germination and flowering time in C. americana have significant additive genetic variation (Galloway et al., 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flowering begins in mid‐summer and fruits ripen and dehisce throughout the fall. Seeds disperse when fruits mature (Galloway & Burgess, 2009) and are nondormant at maturity (Baskin & Baskin, 1984), so the reproductive phenology of maternal plants directly influences offspring germination season (Galloway, 2002; Galloway & Burgess, 2009, 2012). Germination and flowering time in C. americana have significant additive genetic variation (Galloway et al., 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Season of germination is influenced by the seed's genetics as well as by maternal flowering time. Early‐flowering plants disperse seeds early, increasing the potential for fall germination of offspring, while seeds of late‐flowering plants are frequently dispersed in late fall when it is cool and are therefore more likely to germinate the following spring (Galloway, 2002; Galloway & Burgess, 2009, 2012). We predict that there is a genetic correlation between timing of germination and flowering, so they provide a coordinated influence on life history schedule (Peiman & Robinson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Stanton, Roy & Thiede (2000) and Stanton, Thiede & Roy (2004) demonstrated that for the annual Sinapsis arvensis, selection favoured earlier reproduction when grown under stressful than under benign environments. An emerging pattern from multiple studies indicates that flowering time can rapidly respond to natural selection (Elzinga et al 2007;Franks, Sim & Weis 2007;Galloway & Burgess 2012), suggesting either ample standing genetic variation for flowering time within populations or ample gene flow between populations with differing phenological set points. The generality of earlier flowering in response to multiple sources of environmental stress suggests that phenology may be an important trait responding to differences in environmental stress, along with growth and competitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…A small change in reproductive success or flowering time can affect plant fitness (e.g. Galloway and Burgess, 2012;Weis et al, 2015), and consequently might alter interactions with populations of pollinators, seed dispersers, or floral herbivores. The role of biotic interactions in shaping plant flowering phenology has been demonstrated for pollinators and herbivores (Elzinga et al, 2007).…”
mentioning
confidence: 99%